Analysis of Ultramafic Rocks Weathering Level Using the Magnetic Susceptibility in Konawe Regency, Southeast Sulawesi, Indonesia - Jahidin; LO. Ngkoimani; LM. Iradat Salihin; Hasria; Erzam S. Hasan; Irfan Ido; Suryawan Asfar (UIR PRESS, 2020)
The Konawe region is part of the Sulawesi Southeast Arm ophiolite belt where ultramafic rocks are exposed in the form of dunite and peridotite. The formation of nickel deposits is closely related to the weathering process of ultramafic rocks as a source rock. Ultramafic rocks exposed to the surface will experience weathering which is influenced by many factors, including in the form of climate change, topography, and existing geological structures. The weathering process in the source rock can influence variations in chemical elements and magnetic properties in laterite soil profiles. For example, the chemical weathering might affect magnetic mineralogy and the physical weathering could affect granulometry as well as the quantity of magnetic minerals in the soil. Condition of weathering of ultramafic rocks (initial, moderate and advanced) can affect nickel content in laterite sediments. The weathering profile study of serpentine mineral is an indication of the lateralization process that occurs in ultramafic rocks and is carried out through petrographic analysis of thin cuts and polish cuts. Determination of weathering level like this is based on the level of weathering of the mineral serpentine. In this study, the determination of the weathering level of ultramafic rocks (initial, moderate, and continued) uses magnetic susceptibility parameter. A total of 232 ultramafic rock core samples obtained from 34 hand samples were taken from different places and weathered levels were analyzed. The results of the research have shown that the magnetic susceptibility of ultramafic rocks in the study area varies, from 580 x 10-6 SI to 4.724 x 10-6 SI. Based on the value of magnetic susceptibility, magnetic minerals contained in ultramafic rock samples are hematite and geotite minerals. This means that the weathering level of ultramafic rock samples is the continued weathering level. The level of continued weathering that occurs in ultramafic rocks in the study area produces nickel laterite deposits with a nickel content of 1.65 - 2.40% in the saprolite zone, 0.42% in the saprock zone, and 0.20 - 0.51% in the basic rock zone (bedrock).